Handbook of Physical Examination in Surgery - Bostancı, Hasan; Kurukahvecioğlu, Osman; Kozan, Ramazan; Göbüt, Hüseyin; Yavuz, Aydın; Dikmen, Kürşat; Leventoğlu, Sezai; Büyükkasap, Çağrı (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-